Is There a “Gestalt Bias” in Indulgence? Subjectively Constructing Food Units Into Wholes (vs. Parts) Increases Desire to Eat and Actual Consumption - Joye, Yannick; Bruyneel, Sabrina; Fennis, Bob M. (Frontiers in Psychology, 2021)
In the present work we extend research into the unit bias effect and its extension – the portion size effect – by demonstrating the existence of a “Gestalt bias”. Drawing on the tenets of Gestalt psychology, we show that a unit bias effect can be observed for food portions that are composed of identical basic units, but which are subjectively grouped into, or perceived as a Gestalt – a larger whole. In three studies, we find that such subjectively constructed food wholes constitute a new (perceptual) unit that is perceived bigger than the units it is constructed from, thereby prompting increased eating and desire to eat.